Flocking for Multiple Ellipsoidal Agents with Limited Communication Ranges. (26th November 2012) - Do, K. D.
Abstract : This paper contributes a design of distributed controllers for flocking of mobile agents with an ellipsoidal shape and a limited communication range. A separation condition for ellipsoidal agents is first derived. Smooth step functions are then introduced. These functions and the separation condition between the ellipsoidal agents are embedded in novel pairwise potential functions to design flocking control algorithms. The proposed flocking design results in (1) smooth controllers despite of the agents' limited communication ranges, (2) no collisions between any agents, (3) asymptotic convergence of each agent's generalized velocity to a desired velocity, and (4) boundedness of the flock size, defined as the sum of all distances between the agents, by a constant.